Border Crossings Through the Eyes of a Female Narrator: Concept Border in Laura Ingalls Wilder’s Literary Discourse - Zaporozhets, Halyna; Stodolinska , Yuliya (East European Journal of Psycholinguistics, 2021)
Many recent studies have focused on the depiction of BORDER from the point of view of cognitive linguistics, gender studies, cultural studies. However, little research has been undertaken to study the books for children that address questions of borderlands, territorial and metaphorical borders in historical and modern fiction among which is Laura Ingalls Wilder’s Little House Series. The objective of this article is to study the portrayal of cultural concept BORDER from the perspective of a female child narrator in Laura Ingalls Wilder’s literary discourse, focusing on the depiction of territorial and metaphorical borders in order to establish the possible influences and interrelations. The multidisciplinary approach that combines the methods and former research findings of such disciplines as cognitive linguistics, psycholinguistics, border studies, discourse studies is implemented to determine the narrator model and the peculiarities of psychonarration in the book series; classify concept BORDER from the point of view of cognitive linguistics and restructure its components; provide an analysis of the figurative and associative layer of the cultural concept BORDER and examine the role of the verbalization of feelings and emotions in the portrayal of territorial and metaphorical border crossings in Wilder’s books. Overall, it is assumed that the female child narrator has been chosen by the author based on the psychological peculiarities of the target audience of the books. The results indicate that the combination of the external and internal forms of psychonarration ensures a clearer portrayal of the female perception of border crossings in the analyzed discourse. The territorial and metaphorical borders depicted in Wilder’s works are interwoven and influenced by historical, biographical, gender, and psychological peculiarities.